2018
DOI: 10.14302/issn.2574-612x.ijpr-18-2246
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Amnesia – A Challenge to Therapy

Abstract: The psychiatric disease of dissociative amnesia is described and illustrated with case reports. It is emphasized that dissociative amnesia has a stress or trauma-related etiology and that affected individuals, contrary to the still dominant clinical belief, are frequently more severely and enduringly affected. That means, most of them show severe retrograde amnesia for their biography, usually accompanied by changes in their personality and sometimes also by alterations in other cognitive and emotive domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We hope to use this case for establishing efficacious clinical guidelines for treating dissociative amnesia with comorbid schizophrenia. Current experimental treatments for dissociative amnesia include selective serotonin reuptake inhibitor (SSRI) and tricyclic antidepressant (TCA) for mood, trauma-focused psychotherapy for memory retrieval, and neuropsychological rehabilitation for chronic management [ 17 ]. ECT in one case has been reported to be successful, the other one precipitating [ 18 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hope to use this case for establishing efficacious clinical guidelines for treating dissociative amnesia with comorbid schizophrenia. Current experimental treatments for dissociative amnesia include selective serotonin reuptake inhibitor (SSRI) and tricyclic antidepressant (TCA) for mood, trauma-focused psychotherapy for memory retrieval, and neuropsychological rehabilitation for chronic management [ 17 ]. ECT in one case has been reported to be successful, the other one precipitating [ 18 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with dissociative amnesia can regain their lost memory early, and for some of them, it might take several years to recover ( 5 , 14 , 19 ). In this case, at this time, it is difficult to predict whether she regains her identity and objective facts associated with her life history.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases of trauma-related stress, both retrograde and anterograde memories are affected along with overall impairment of mental and physical health [26,55]. Studies relating to the frequency of dissociative and psychogenic amnesia have been carried out in 16 countries with rates of prevalence in different countries varying from 0.2 to 7.3% [56]. This large variation in the epidemiology may partly be explained by a lack of standard testing.…”
Section: Epidemiology Of Psychogenic Amnesiamentioning
confidence: 99%
“…This large variation in the epidemiology may partly be explained by a lack of standard testing. Therefore, combining social research with neuroimaging data and neurobiological studies of this disorder is suggested to improve understanding of the debilitating impact on its sufferers, and indigenous Australian communities in general [56].…”
Section: Epidemiology Of Psychogenic Amnesiamentioning
confidence: 99%